EFFECT OF CLINICAL Klebsiella pneumoniae EXTRACTED MELANIN ON SOME IMMUNE ASPECTS IN MICE - & Alaubydi, Saud (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2019)
Melanin is a pigmented material varies from yellow to black color dependent on the type of melanin. Not all the microorganisms can produce this material, most industrial researchers are looked after about melanin that produced from environmental microorganisms and little is known about from pathogenic bacteria and its role in pathogenesis. Therefore this study is aimed to focus on the role of melanin produces by one pathogenic bacteria(Klebsiella pneumoniae  ) isolated from an infected wound on host immune responses.The results of this study showed, that the increasing melanin concentration leads to decrease in the phagocytic index. and in vivo tests are done by using different concentration of extracted microbial melanin, These concentrations showed variable effects on tested cytokines( IL-1β , IL-12 , TNF-α , IL-10 , IFN-γ and  IL-4) In conclusion, microbial melanin is act as virulence factor throughout suppress the most important pro-inflammatory cytokines and that squeal to counteract immune responses.